Efektivitas Model Pembelajaran Blended Learning Pada Mahasiswa Program Studi Diploma III Kebidanan Di Fakultas Kesehatan Universitas YPIB Majalengka - Yuwansyah, Yeti; Sholihah, Try Fatmah; Suyanti, Suyanti (Akademi Kebidanan Bunga Husada Samarinda, 2022)
The number of obstacles found in online learning during the Covid-19 pandemic is supported by the Circular of the Minister of Education and Culture of the Republic of Indonesia Number 4 of 2021 concerning the Implementation of Face-to-face Learning for the Academic Year of 2021/2022. This study aims to determine the effectiveness of the Blended Learning Model for Diploma III Midwifery Study Program students at the Faculty of Health, YPIB Majalengka University in 2022. This type of research is quantitative descriptive research. The sample in this study was all students of level I, II, and III Midwifery Study Program at YPIB Majalengka University as many as 53 people consisting of 23 levels I, 22 level II, and 23 level III (Probability Proportional to Size Sampling). This research was carried out at the Faculty of Health, YPIB Majalengka University in 2022 in February-April 2022. Univariate analysis used a frequency distribution. The results showed that most (89.7%) students stated that they strongly agreed with the effectiveness of the blended learning model, a small part (1.5%) of students did not agree with the definition of blended learning, a small part (11.8%) of students stated that they did not agree with the definition of blended learning. blended learning component, a small portion (5.9%) of students stated that they did not agree with the key of blended learning, a small portion (8.8%) of students stated that they did not agree with the characteristics of blended learning, a small portion (1.5%) of students stated that they did not agree with the benefits of blended learning, a small portion (7.4%) of students stated that they did not agree with the advantages and disadvantages of blended learning. The lecturer needs to first arrange the schedule and implementation time between face-to-face learning and online learning. Lecturers also need to optimize learning methods and designs that are carried out online.